Infectious endocarditis and vertebral osteomyelitis caused by Moraxella catarrhalis - Maierean, Serban M (BMJ Publishing Group, 2019)

(untitled) (BMJ Case Rep)
Moraxella catarrhalis frequently colonises the oropharynges of healthy individuals. Disease is usually limited to the oropharynx, upper airways and lower airways in patients with predisposing conditions. The pathogen rarely causes more invasive disease. We present the case of a 65-year-old woman with Crohn’s disease on azathioprine, who was diagnosed with native valve M. catarrhalis endocarditis and vertebral osteomyelitis several weeks after an upper respiratory tract infection. She presented to hospital with 5 weeks of worsening malaise, nausea, relapsing fevers, weight loss, acute-on-chronic exacerbation of lower back pain and diffuse myalgia. Transoesophageal echocardiogram showed a 12 mm vegetation on her mitral valve, contrast-enhanced MRI was consistent with L4 osteomyelitis and blood cultures were persistently positive for M. catarrhalis. She was initially treated with ceftriaxone 2 g intravenously daily, and although her symptoms initially resolved, she experienced a relapse of osteomyelitis with L3 extension a few weeks after treatment discontinuation.